Belize : 2005 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2005)
This 2005 Article IV Consultation highlights that the Belizean economy grew by 4 1\2 percent in 2004, mainly reflecting strong performance in the agriculture, fisheries, and tourism sectors. Inflation remained subdued at about 3 percent. The overall fiscal deficit of the central government, however, widened to 8 3/4 percent of GDP in FY04/05. Executive Directors have underscored the urgency of addressing these imbalances to safeguard the country's international reserves and ensure the sustainability of the pegged exchange rate system.